Klasifikasi Batuan Beku Gabbro Pada Citra Sayatan Tipis Menggunakan Multilevel Otsu’s Thresholding - Muhammad Dzulfikar Fauzi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2017)
The image of a thin section of rock is a rock or mineral observation methods. The mineral content of rocks can be used to determine rock types and names of these rocks. Thin section making observations difficult if only using polarizing microscopy, the ability of the human eyes can not identify in detail. Therefore, the analysis and identification of minerals to be more easily done with the help of digital image processing algorithms using Multilevel Otsu's Thresholding to determine the abundance of igneous minerals. The data used in this study using the image of a thin section of igneous rock acquired from use polarizing microscope with a magnification of 10x. Preprocessing is performed with two different treatment is grayscale and grayscale with k-means to determine the maximum results. The next stage of the processing is done Multilevel Otsu's Thresholding segmentation with two threshold values. Further analysis of the results of segmentation to determine the abundance of minerals. The results of calculations and analysis has been done on the preprocessing using grayscale and grayscale with k-means then done Multilevel Otsu's Thresholding segmentation has the highest accuracy of 40% and 33.57%. Of the two treatments can be concluded that the use of k-means on the preprocessing have an influence on image processing thin section gabbro igneous rock types with the highest accuracy values of the two treatments at 40% by using the kmeans preprocessing with a value of k = 7.